2010
DOI: 10.1186/1758-2555-2-18
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of total hip arthroplasty after hip arthroscopy in osteoarthritic patients

Abstract: ObjectiveTo assess the incidence of total hip arthroplasty (THA) in osteoarthritic patients who were treated by arthroscopic debridement and to evaluate factors that might influence the time interval from the first hip arthroscopy to THA.DesignRetrospective clinical seriesMethodsFollow-up data and surgical reports were retrieved from 564 records of osteoarthritic patients that have had hip arthroscopy between the years 2002 to 2009 with a mean follow-up time of 3.2 years (range, 1-6.4 years). The time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 17 publications
3
55
1
1
Order By: Relevance
“…Several articles have used Tönnis grade as a descriptive for outcome studies [6,9,13,15,16,22,25]. One recent article excluded patients with Tönnis Grade 2 or greater and greater than 50% narrowing of the joint space and still had 8% conversion to THA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have used Tönnis grade as a descriptive for outcome studies [6,9,13,15,16,22,25]. One recent article excluded patients with Tönnis Grade 2 or greater and greater than 50% narrowing of the joint space and still had 8% conversion to THA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Specific to the severity of the chondral injury, other authors have reported a relationship between the severity of the chondral injury and treatment failure [3,6,13,17]. These reports specifically describe large delaminated cartilage lesions as being associated with failure although specific treatment of these lesions was variably performed and reported.…”
Section: Discussionmentioning
confidence: 99%
“…The observed area and thickness of articular cartilage loss were graded as follows: Grade 0 = no degeneration; Grade 1 = localized articular cartilage loss (partial-thickness acetabulum); Grade 2 = partial-thickness loss at the acetabulum and femoral head (\ 30% of the acetabular anterior wall width involved, with full-thickness articular cartilage loss); Grade 3 = full-thickness acetabulum ([ 30%) and partialthickness femoral head; and Grade 4 = full-thickness loss on both surfaces [9]. This grading system was based on the early Outerbridge system for grading patellofemoral degeneration [19].…”
Section: Methodsmentioning
confidence: 99%